The Influence of Audit Quality, Company Financial Condition, Previous Year's Audit Opinion, Company Growth on Acceptance of Going Concern Audit Opinion in Companies Listed on the IDX - Maharani, Amalina; Yandi, Andri (Dinasti Accounting Review, 2023)
The responsibilities of auditors currently do not only focus on assessing the fairness of financial statements and detecting fraud, but also on assessing the company's ability to maintain its survival. This is due to the demands of the shareholders to the auditor to provide early warning about the prospects of a company as consideration before deciding an investment decision. The research's goals were to examine the effect of the audit opinion received in the quality of the audit, financial condition of the company, previous years against the acceptance and the company's growth of a going concern opinion. The samples of this research were the companies that suffered losses three years in a row and were listed on the Indonesian Stock Exchange (ISE) from 2011 to 2013. The hypotheses were tested using a logistic regression method. The results of this research showed that the quality of audits and previous audit opinions had a significant effect, but the financial variables and growth companies weren't significantly influenced by going concern opinions.